Perbedaan air rebusan daun seledri dan air rebusan daun salam terhadap penurunan tekanan darah pada pra lansia dengan hipertensi primer - Asep Badrujamaludin; Budiman Budiman; Tifany Desty Erisandi (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
The effect of celery (apium graveolens) leaf and bay leaf (Syzygium polyanthum wight) on the blood pressure in pre-elderly with primary hypertensionBackground: Hypertension, also known as high blood pressure, is as medical condition in which the blood pressure in arteries is persistently elevated. This condition can increase risk of cardiovascular diseases such as stroke, kidney failure, heart attack, and kidney damage. Hypertension requires proper treatment to prevent uncontrolled blood pressure that can cause damaged organs. One of traditional treatment for hypertension is using celery leaves (Apium graveolens L) and bay leaves (Syzygium polyantum).Purpose: This research is to determine the difference of blood pressure after the consumption of boiled water celery leaves and bay leaves in pre-elderly with hypertension at Cigugur Tengah Public Health Center.Method: The type of this research is the numerical comparative analytic with Quasi Experiment design with Non Equivalent Control Group Design. This research used purposive sampling technique using 22 responden with inclusion and exclusion criteria. Data collection was performed by measuring the blood pressure before and after the consumption of celery leaves and bay leaves boiled water that consume twice a day in one week. The data are processed including univariate and bivariate data analysis.Results: The statistical result of T-independent test obtain p value of 0,365 > α (0,05) for the systolic blood pressure and 0,574 > α (0,05) for diastolic blood pressure.Conclusion: Result showed that there is no average difference of blood pressure in group intervention boiled water of celery leaves and bay leaves after consumption of boiled water celery leaves and bay leaves. However, both intervention have decreased blood pressure of hypertension patient.Suggestion of this research is to consume boiled water of celery leaves and bay leaves for longer time as additional therapy for hypertension patient.Keywords: Pre-elderly; Celery leaf; Bay leaf; Primary hypertensionPendahuluan: Hipertensi merupakan suatu keadaan tekanan darah yang tinggi di dalam arteri, sehingga meningkatkan risiko terhadap penyakit-penyakit yang berhubungan dengan kardiovaskuler seperti stroke, gagal ginjal, serangan jantung, dan kerusakan ginjal. Hipertensi membutuhkan penanganan yang tepat untuk mencegah tidak terkontrolnya tekanan darah yang dapat menyebabkan organ tubuh menjadi rusak. Salah satu pengobatan alami hipertensi yang dilakukan adalah pengobatan dengan menggunakan daun seledri (Apium graveolens L) dan daun salam (Syzygium polyanthum).Tujuan: Untuk mengetahui perbedaan tekanan darah sesudah pemberian air rebusan daun seledri dan air rebusan daun salam terhadap penurun tekanan darah pada pra lansia dengan hipertensi primerMetode: Analitik komparatif numerik tidak berpasangan dengan desain Quasi Eksperimen dengan rancangan Non Equivalent Control Group. Pengambilan sampel dilakukan secara teknik purposive sampling sebanyak 22 responden. Pengumpulan data dilakukan dengan cara mengukur tekanan darah responden sebelum dan sesudah diberikan perlakuan dua kali sehari selama satu minggu. Pengolahan dengan menggunkan uji T-independent diperoleh nilai p value tekanan darah sistolik 0,365 > α (0,05) dan p value tekanan darah diastolik 0,574 > α (0,05).Hasil: Tidak terdapat perbedaan yang signifikan rerata tekanan darah pada kelompok intervensi baik yang diberikan air rebusan daun seledri dan air rebusan daun salam.Simpulan: Terdapat penurunan tekanan darah dari kedua kelompok intervensi tersebut bagi penderita hipertensi. Saran dari penelitian ini diharapkan penderita yang mengalami hipertensi dapat mengaplikasikan air rebusan daun seledri dan air rebusan daun salam dalam kurun waktu lama sebagai tambahan terapi untuk hipertensi.